The Concept of Patience in Adolescents According to The Perspective of Islamic Counseling Guidance - Syahrullah Syahrullah; Raghib Filhaq; Dihartawan Dihartawan; Saiful Bahri (Fakultas Kesehatan Masyarakat Universitas Muhamamdiyah Jakarta, 2022)
This article discusses the concept of patience in adolescents according to the perspective of Islamic counseling guidance. The method used is descriptive analysis, by exploring all sources related to the concept of patience in adolescents according to the perspective of Islamic counseling guidance. e. Islam is allah's shari'a for humans, with the provision of sharia that man worships as a form of embodiment to serve Allah swt. In order for humans to restrain themselves or limit the soul from all passions so that the realization of something good known as the concept of patience. Of course, there will be no realization of Islamic sharia without self-forging efforts, and for that it is necessary for the role of Islamic counseling to be introduced from generation to generation to the next generation. Islamic counseling has a huge hand in a teenager. Islam as a religion full of Divine values, will provide positive value in the teenager. That way, Islamic counseling plays an important role in adolescents in this era. Human beings who basically understand the values of the Godhead that exist in them.